The EU Divorce Jurisdiction of Brussels IIB Regulation and Its Implementation in Austria - Bastomi, Ahmad (Universitas Islam Malang, 2024)
To accommodate the needs of its citizens in building relationships across borders, the EU has provided several regulations. Since its first establishment in 2000, the EU regulations on divorce and legal separation jurisdiction have been amended twice. There are some significant changes in this jurisdiction, from its original regulation in 2000 to its amendment version in 2003 up to the current version that was established in 2019. This paper tries to investigate the implementation of the current ruling EU instrument in Austria through three approaches by evaluating: 1) the infringement cases, 2) preliminary ruling proceedings, and 3) further official actions conducted by Austria. It can be concluded that Austria has never been accused of any infringements of the three regulations. The court judgments of the two proceedings of preliminary ruling submitted by Austrian courts concerning Brussels IIA Regulation are also in accordance with the regulated law of EC No 2201/2003. The establishment of an introductory decree on the summary and legal explanations of the Council Regulation EU No 1111/2019 by Austria is a very good practice that can be adopted by other EU member states. Therefore, this paper suggests that Austria has effectively implemented the 2019 EU instrument.